2007
DOI: 10.1002/cncr.22601
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine triphosphate‐based chemotherapy response assay (ATP‐CRA)‐guided platinum‐based 2‐drug chemotherapy for unresectable nonsmall‐cell lung cancer

Abstract: BACKGROUND.The study investigated correlations between adenosine triphosphate / chemotherapy response assay (ATP‐CRA) and clinical outcomes after ATP‐CRA‐guided platinum‐based chemotherapy for unresectable nonsmall‐cell lung cancer (NSCLC).METHODS.The authors performed an in vitro chemosensitivity test, ATP‐CRA, to evaluate the chemosensitivities of anticancer drugs such as cisplatin, carboplatin, paclitaxel, docetaxel, gemcitabine, and vinorelbine for chemonaive, unresectable NSCLC. The cell death rate was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 27 publications
2
40
1
2
Order By: Relevance
“…However, as new agents and chemotherapy regimens are accepted for various kinds of cancers in clinical situations, new sensitivity criteria should be defined. With regard to gemcitabine, 16.9 lg/ml gemcitabine concentration and greater than 30% inhibition (inhibition rate = 100 -T/C ratio; in other words, T/C ratio less than 70%) was reported as the sensitivity criterion for advanced non-small cell lung cancer [7]. In this study, gemcitabine concentration was 20 lg/ml, according to the peak plasma concentration of gemcitabine [19], but similar Fig.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, as new agents and chemotherapy regimens are accepted for various kinds of cancers in clinical situations, new sensitivity criteria should be defined. With regard to gemcitabine, 16.9 lg/ml gemcitabine concentration and greater than 30% inhibition (inhibition rate = 100 -T/C ratio; in other words, T/C ratio less than 70%) was reported as the sensitivity criterion for advanced non-small cell lung cancer [7]. In this study, gemcitabine concentration was 20 lg/ml, according to the peak plasma concentration of gemcitabine [19], but similar Fig.…”
Section: Discussionmentioning
confidence: 79%
“…If the T/C ratio is low, we expect good therapeutic efficacy. The usefulness of chemosensitivity testing has been reported for various cancers, for example those of the gastrointestinal tract, lung, ovary, and breast, and malignant melanoma [5][6][7][8][9][10]. For gastric cancer, especially, the reported sensitivity, specificity, and accuracy of chemosensitivity testing are, respectively, 82.7, 70.7, and 73.6% [11].…”
Section: Introductionmentioning
confidence: 98%
“…ATP-based chemotherapy response assay has been used to guide the outcome of platinum-based drug chemotherapy for nonresectable non-small-cell lung cancer (Moon et al, 2007(Moon et al, , 2009. It has been suggested that tumor-infiltrating immune cells can benefit the tumor by producing factors that promote angiogenesis and suppress immunity; adenosine levels are high in tumors.…”
Section: F Lung Cancermentioning
confidence: 99%
“…ATP-based ITRT determines the degree of cell inhibition by comparing the ATP remaining in the test compared to the control wells to predict the response to each chemotherapeutic agent. Recently, an ATP-based chemotherapy response assay (ATP-CRA), a modified form of the ATP-based ITRT, has been proven to be useful in lung and breast cancer [2,3] . Since results can be obtained from a small amount of tissue in a short period of time, the ATP-CRA enables to accelerate treatment initiation to meet clinical requirements.…”
mentioning
confidence: 99%